From Bestial to Human: Neo-Mythological Reinterpretations of the Image of Delilah in Russian Literature at the Turn of the 20th-21st Centuries - Nataļja Šroma (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The article examines one of the eternal images of the world culture in a diachronic aspect, namely the interpretation and reinterpretation of the image of Delilah in Russian literature, primarily in poetry, from the 19th century to the present day. The novelty of the article involves the introduction into the scientific context of a number of neo-mythological texts and the provided scholarly commentary, as well as the study of the poetics of the myth and neo-myth with an emphasis on the ethical aspect in the context of ideas of Dmitry Ovsyaniko-Kulikovsky.